Applying the Concept of Adaptive Reuse in Changing the Function of UPT SMP Negeri 30 Gresik School Building into Elderly Service Facilities - Saidha Nur Rachmawati; Mufidah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The increasing elderly population in Gresik Regency has created a growing demand for adequate elderly care facilities. On the other hand, the former UPT public junior high school 30 Gresik building is an underutilized public asset with the potential for functional transformation. This study aims to analyze the implementation of the adaptive reuse concept in converting the former UPT public junior high school 30 Gresik building into an elderly care facility. A qualitative descriptive method with a case study approach was employed through field observations, documentation, and literature review. The results indicate that the building has significant potential for reuse through the preservation of its existing structure, spatial function transformation, and improved accessibility to meet the needs of elderly users. The implementation of adaptive reuse offers a sustainable alternative for optimizing public assets while supporting the development of elderly care facilities in Gresik Regency.